The Dragon and the Anaconda : China, Brazil and the power balance in the Americas - Horta, Loro (2016)
In April 2009 China surpassed the United States by $400 million as Brazil’s largest trading partner. This development signifies the changing balance of power in the region, with implications for Brazil, which is a major player in the Americas.